The influence of online shopping reviews on customer purchase intention - The case of Alibaba online shop in China - Guo, Meng (2016)
This dissertation attempts to investigate the factors of customer online reviews influence customer purchase intention in the case of Taobao and Tmall, the most popular online shopping websites in China. Data was collected through a series of interviews with twenty individuals who have plenty of online shopping experience in China, and majorly shopping on Taobao and Tmall. The research was conducted by semi-structured interviews following an interview guide covers the main topic and interviewees own experience. In this study, a thematic analysis was adopted to analyze the interview data.